Rancangan Bangun Aplikasi Point Of Sales (POS) Pada CV. Safira Telekomindo Berbasis Java Netbeans - Wifaqul Azmi; Mohammad Fazrie; Fery Rahmawan Asma (Fakultas Teknologi Informasi Institut Teknologi Adhi Tama Surabaya, 2020)
Abstract. A retail store has difficulty calculating transactions quickly and accurately, less good management of goods, management of suppliers that are still manual, calculating profits and transactions in a long time and processing long transactions. To solve this problem, a Point of Sale application was made. Point of sale itself is a system that allows the holding of the transaction process. Starting with the system design stage includes making context diagrams, data flow diagrams, entity relationship diagrams and database design. This application was created using the Java Netbeans programming language and integrated with MySQL as a database for storing data. The application has features such as data processing of goods, supplier data processing, employee data management, view transaction data, conduct sales transactions, cancel sales items, calculate and print receipts. The purpose of this research is to create a neatly organized and good system so that can make it easier for users to complete their work. This application is expected to help the work of employees on the CV. Safira Telekomindo has become more thorough and effective.Keywords : Design and Build Point of Sales Application, Safira Telekomindo. Java, MySQL. Abstrak. Sebuah toko retail memiliki kesulitan untuk menghitung transaksi dengan cepat dan akurat, manajemen barang yang kurang bagus, manajemen supplier yang masih manual, menghitung laba dan transaksi dalam waktu yang lama dan pemrosesan transaksi yang lama. Untuk menyelesaikan permasalahan tersebut dibuatlah sebuah aplikasi Point of Sale. Point of sale sendiri merupakan sebuah sistem yang memungkinkan diadakannya proses transaksi Dimulai dengan tahap perancangan sistem meliputi pembuatan context diagram, data flow diagram, entity relationship diagram dan perancangan database. Aplikasi ini dibuat dengan menggunakan bahasa pemrograman Java Netbeans dan terintegrasi dengan MySQL sebagai database Untuk menyimpan data. Aplikasi tersebut mempunyai fitur seperti pengolahan data barang, pengolahan data supplier, pengelolaan data karyawan, melihat data transaksi, melakukan transaksi penjualan, pembatalan item penjualan, penghitungan dan pencetakan struk.Tujuan dari penelitian ini adalah untuk membuat sebuah sistem yang terorganisasi dengan rapih dan baik agar dapat memudahkan pengguna dalam menyelesaikan pekerjaanya. Aplikasi ini diharapkan dapat membantu pekerjaan karyawan pada CV. Safira Telekomindo menjadi lebih teliti dan efektif.Kata Kunci : Rancang Bangun Aplikasi Point Of Sales, Safira Telekomindo. Java, MySQL.